Village hatchery unit: A successful model for sustainable poultry farming - Mooventhan, P.; Verma, L. K.; Singh, Uttam; Ghosh, P. K.; Mondal, K. K. (Indian Farming, 2025)
The Village Hatchery Unit (VHU) model is a sustainable approach to poultry farming developed under the Farmer FIRST Programme. It addresses the challenge of limited access to healthy chicks for small-scale and backyard farmers by providing village-based hatchery solutions. These VHUs empower local farmers and women’s self-help groups to hatch chicks at the community level, thereby reducing reliance on industrial hatcheries. VHUs foster self-sufficiency and support local economies, promoting sustainable practices in rural poultry farming. The model leverages automated incubators, proper hatchery management, and community-driven initiatives, ensuring the timely availability of quality chicks and enhancing local poultry production. This sustainable model is a practical and profitable solution, encouraging ecological balance, economic viability, and social equity in rural poultry farming.